Optimization of the Development Strategy for the Sidodadi Small Scale Tofu Industry in Tinalan, Kediri, to Enhance Competitiveness - Dedy Kunhadi; Dyah Pelitawati; Mira Gayatri Kartika; Ony Kurniawati (G-Tech: Jurnal Teknologi Terapan, 2025)
The problems faced by Sidodadi Kediri tofu small industry are the tight competition from similar products, lack of innovation of the product process, and lack of understanding of effective marketing techniques, this study aims to provide policy recommendations that can support the development of Sidodadi tofu small industry in an effort to improve competitiveness. The data collection process uses the delphi method, where the delphi method is a technique used to collect and analyze opinions from a group of experts or experts who are in accordance with the topic under study. The main purpose of this method is to reach an agreement on the development of the Sidodadi Tofu small industry to improve competitiveness. The approach used to solve this problem includes analysis using the IFE Matrix, EFE Matrix, IE Matrix, SWOT, and QSPM. The results of this study emphasize the importance of quality-based product innovation that can increase customer satisfaction and create a positive reputation. In addition, diversification of distribution channels is key to expanding market reach, by utilizing online sales and partnerships with various restaurants. By implementing these strategies, the Sidodadi Tofu industry is expected to improve its performance, competitiveness, and business sustainability in the future.